The Nepal-Tibet War (1855-56): Operational Planning and Logistical Management (Voice of History, 2025)
The Nepal-Tibet War of 1855–56 represents an important yet often overlooked episode in the military and diplomatic history of the Himalayan region. Sparked by longstanding grievances over trade rights, territorial encroachments, and political tensions, the conflict was initiated by Nepal at a time when both Tibet and the Qing Empire were beset by internal instability. This study explores the multifaceted causes of the war, including Nepal’s efforts to reclaim lost privileges, deteriorating cross-border relations, and the influence of shifting regional power dynamics involving British India. Despite its relatively short duration, the war posed immense operational and logistical challenges due to the formidable Himalayan terrain, harsh climate, and limited infrastructure. Nepal’s military success was made possible through strategic foresight, rigorous planning, and extensive resource mobilization, including the construction of decentralized supply depots, integration of local manpower, and the deployment of medical services along the frontlines. By analyzing the sequence of military campaigns, the leadership of key commanders, and the eventual signing of the Treaty of Thapathali, this paper argues that while Nepal secured notable tactical victories, the prolonged strain on resources necessitated a negotiated peace. The treaty granted Nepal certain trade and diplomatic concessions and reaffirmed its influence in Tibet, though it did not substantially disrupt the broader geopolitical balance. Drawing upon archival materials, historical correspondence, and recent historiographical interpretations, this paper positions the war as a defining moment in Nepal’s assertion of autonomy, military modernisation, and evolving diplomatic posture vis-à-vis Tibet and the weakening Qing authority.